Risk Awareness and Quality of Life of a Coastal Community Exposed to Environmental Hazards (Luanda, Angola) - Nogueira, Patrícia; Faria, Silvana; Mosley, Benjamin A.; Domingues, Rita B. (Journal of Tourism, Sustainability and Well-being, 2021)
Luanda Bay and Mussulo Lagoon, situated in Luanda (Angola), are two coastal ecosystems highly sensitive to environmental issues, such as climate change, water pollution, eutrophication, and harmful algal blooms. These environmental problems can severely affect the quality of life of coastal populations. In this study, we aim to evaluate several psychological variables, such as environmental risk perception and awareness, sense of place, environmental attitudes, and the overall quality of life of the coastal community in these areas, using a comprehensive questionnaire applied to residents and other ecosystem users. Results indicate that most respondents considered that they possess high knowledge about climate change, water pollution, and ingestion of contaminated seafood. However, regarding eutrophication and harmful algal blooms, most participants reported a low/moderate knowledge. Life experience and the media were reported as the most relevant sources of information on environmental problems. Respondents indicated a moderate risk perception towards environmental risks, and a moderate/high emotional attachment to the place. Residents’ perceived quality of life was moderate/good in terms of physical and psychological health, and social relationships, but the environmental component was perceived as weak. Results suggest that improvements in the natural environment are needed to increase the quality of life in these ecosystems.